Pengaruh Good Corporate Governance, Profitabilitas, dan Leverage Terhadap Nilai Perusahaan pada Sektor Energi di BEI Tahun 2021-2024 - Aisyah Saharani; Budi Setiawan; Emilda Emilda (Journal of Indonesian Economic Research, 2026)
This study aims to analyze the effect of Good Corporate Governance (GCG), profitability, and leverage on firm value in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The study uses a quantitative approach with an explanatory research design and secondary data obtained from annual financial reports and corporate governance reports. The sample was selected using purposive sampling techniques from energy sector companies listed on the IDX. Data analysis was carried out using multiple linear regression analysis after fulfilling the classical assumption tests. The results indicate that Good Corporate Governance, profitability, and leverage positively and significantly influence firm value, both partially and simultaneously. Therefore, the implementation of good corporate governance, increased profitability, and optimal leverage management are important factors in improving the firm value of energy sector companies in Indonesia.